Erlotinib and Concurrent Chemoradiation in Pretreated NSCLC Patients: Radiobiological Basis and Clinical Results. (4th August 2013) - Ramella, Sara; Alberti, Antonio Maria; Cammilluzzi, Eugenio; Fiore, Michele; Ippolito, Edy; Greco, Carlo; De Quarto, Angelo Luca; Ramponi, Sara; Apolone, Giovanni; Trodella, Lucio; Cesario, Alfredo; D'Angelillo, Rolando Maria
Abstract : Aims . To establish feasibility of the combination of Erlotinib and concurrent chemoradiation in pre-treated patients with locally advanced or metastatic NSCLC. Materials and Methods. Data regarding 60 consecutive patients with NSCLC previously treated with chemotherapy alone were prospectically collected. All patients started Erlotinib concurrently with chemotherapy and radiation delivered to primary tumor. These data were retrospectively analyzed (observational study). Feasibility and toxicity were the primary endpoints, with response rate and progression being the secondary ones, while survival data are reported just as exploratory analysis. The EGFR mutational status was recorded in 32% of cases and it was always wild type. Results . Compliance to the combination protocol was good. Grade 3-4 esophagitis and acute lung toxicity occurred in 2% and 8% of patients, respectively. No progressive disease was recorded in the majority of cases (65%). Median OS and PFS were 23.3 and 4.7 months, respectively. Patients not responding to chemotherapy administered prior to chemoradiation achieved an objective response rate of 53.3% and complete response in 13.3% of cases. Conclusions . The addition of Erlotinib to chemoradiation in inoperable NSCLCs is feasible with interesting efficacy profile. These preliminary results warrant further investigation in patients with locally advanced nonmetastatic NSCLC with EGFR mutations.